Speed control of induction motor with broken bars using sliding mode control (SMC) based to on type-2 fuzzy logic controller (T2FLC) - Djameleddine. Djafar (Université de M'sila, 2021)
The traditional control of induction motor is not enough, because it lacks robustness, especially when the demand for accuracy and other dynamic characteristics of the system are of better performance in nowadays industry. One of the most spreader problems of the induction motor that limits the performance of the speed control is the broken rotor bars. For Improving performance of the induction motor of broken rotor bars, sliding mode control based on fuzzy logic type-2 is analyzed within this research paper. Fuzzy logic is one of the methods that relay on artificial intelligence, and which does not require a mathematical model of the system as the traditional control does. Artificial intelligence is the most used one, especially when it comes to non-linear systems as the motor drive one.